2021
DOI: 10.1128/aac.02267-20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Oral Fosfomycin for Asymptomatic Bacteriuria in Kidney Transplant Recipients: Results from a Spanish Multicenter Cohort

Abstract: Current guidelines recommend against systematic screening or treating asymptomatic bacteriuria (AB) among kidney transplant (KT) recipients, although the evidence regarding episodes occurring early after transplantation or in the presence of anatomical abnormalities is inconclusive. Oral fosfomycin may constitute a good option for the treatment of post-transplant AB, particularly due to the emergence of multidrug-resistant (MDR) uropathogens. Available clinical evidence supporting its use in this specific sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…Furthermore, it is hard to tell if the other adverse reactions reported (fatigue, anorexia, dyspnea and tachycardia) were caused by the antibiotic itself, rather than by the concomitant medications and clinical conditions. These data are consistent with the current literature, which shows a favorable safety profile of fosfomycin, with adverse reactions generally mild and not requiring discontinuation of treatment, [22][23][24][25] although studies in exclusively pediatric populations are still scarce. 26 Our study has many limitations.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it is hard to tell if the other adverse reactions reported (fatigue, anorexia, dyspnea and tachycardia) were caused by the antibiotic itself, rather than by the concomitant medications and clinical conditions. These data are consistent with the current literature, which shows a favorable safety profile of fosfomycin, with adverse reactions generally mild and not requiring discontinuation of treatment, [22][23][24][25] although studies in exclusively pediatric populations are still scarce. 26 Our study has many limitations.…”
Section: Discussionsupporting
confidence: 91%
“…Half of the isolates had an MDR phenotype (ESBL‐E in 14.0%, CRE in 3.5%), although the odds of microbiological cure were not decreased in these episodes (71.4%) 114 . Similar results have been also reported for asymptomatic bacteriuria within the first post‐transplant months 115 . Concordant with these observational experiences, the administration of a single 4‐g dose of intravenous fosfomycin disodium before the placement or removal of a urinary catheter or a double‐J ureteral stent resulted in a lower incidence of symptomatic UTI or asymptomatic bacteriuria during the first weeks after KT as compared with placebo 116 .…”
Section: Therapeutic Options For Esbl‐e and Cre Infections In The Sot...supporting
confidence: 68%
“…114 Similar results have been also reported for asymptomatic bacteriuria within the first post-transplant months. 115 Concordant with these observational experiences, the administration of a single 4-g dose of intravenous fosfomycin disodium before the placement or removal of a urinary catheter or a double-J ureteral stent resulted in a lower incidence of symptomatic UTI or asymptomatic bacteriuria during the first weeks after KT as compared with placebo. 116 Evidence supporting the use of intravenous fosfomycin for serious GNB infection is still emerging.…”
Section: Non β-Lactam Alternativesmentioning
confidence: 72%
“…Only a single study of 185 KTx recipients showed that untreated ASB was significantly more likely to be followed by a subsequent episode of symptomatic UTI in the same organism in comparison to cases of treated ASB [ 40 ]. In a recently published study by Ruiz-Ruigomez, which assessed the rate of microbiological eradication after treatment of ASB episodes with fosfomycin, the treatment failure rate exceeded 40% [ 55 ]. Moreover, the routine use of trimethoprim-sulfametoxazole prophylaxis did not reduce the prevalence of ASB [ 53 ].…”
Section: Managementmentioning
confidence: 99%